Melatih Konsentrasi Melalui Permainan Sensorik Motorik Media Puzzel Pada Anak di Taman Kanak-Kanak Permata Hati Desa Limbang Jaya I - Itryah, Itryah; Nasywa Putri Sahirah (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
The golden age according to the mentossori approach (Jadi, R. 2020) is a period in the development of the child where he has the potential to learn and understand new things easily and quickly. This activity aims to train early childhood concentration skills through motor sensory games using puzzle media at Permata Hati Kindergarten, Limbang Jaya 1. Children's concentration problems, such as being easily distracted or having difficulty completing tasks, are the basis for the implementation of this program. The activity began with observation to understand the basic condition of the child and then gradually applied puzzle media for interactive learning. The methods used include education in the form of games and direct observation. The results of this activity show that puzzle games can improve children's concentration, fine motor coordination, problem-solving ability and emotional control. From this activity, children are more focused, independent, and motivated when completing tasks either individually or in groups.